Kidney and Urinary Tract Involvement in Kawasaki Disease - Toru Watanabe (International Journal of Pediatrics)
Kawasaki disease (KD) is a systemic vasculitis and can develop multiple organ injuries including kidney and urinary tract involvement. These disorders include pyuria, prerenal acute kidney injury (AKI), renal AKI caused by tubulointerstitial nephritis (TIN), hemolytic uremic syndrome (HUS), and immune-complex mediated nephropathy, renal AKI associated with either Kawasaki disease shock syndrome or unknown causes, acute nephritic syndrome (ANS), nephrotic syndrome (NS), renal tubular abnormalities, renal abnormalities in imaging studies, and renal artery lesions (aneurysms and stenosis). Pyuria is common in KD and originates from the urethra and/or the kidney. TIN with AKI and renal tubular abnormalities probably result from renal parenchymal inflammation caused by T-cell activation. HUS and renal artery lesions are caused by vascular endothelial injuries resulting from vasculitis. Some patients with ANS have immunological abnormalities associated with immune-complex formation. Nephromegaly and renal parenchymal inflammatory foci are detected frequently in patients with KD by renal ultrasonography and renal scintigraphy, respectively. Although the precise pathogenesis of KD is not completely understood, renal vasculitis, immune-complex mediated kidney injuries, or T-cell immune-regulatory abnormalities have been proposed as possible mechanisms for the development of kidney and urinary tract injuries.